Investigating the Effect of Picture Story Book on Grade Ten Students’ Reading Comprehension Ability - Sixteen Amalia; Alimatun NA; Enci Zharkasih (Lingua, 2020)
As a foreign language, some students still get some difficulties to learn English, especially in English Reading. An attractive media such as Picture Story Book is expected to develop the students reading comprehension ability. The research method that was used in this research was true experimental and the research design was pot test only control group design. To gather the data the researcher used instrument in the form of multiple choice 30 questions. The samples of this research was grade ten consisting 66 students, which is taken from the population by using cluster random sampling technique. The students are divided into two classes, 33 in experimental class and 33 in control class. The students of experimental class were taught by using Picture Story Book while the control class were taught without Picture Story Book. The analysis used SPSS based independent sample T-Test Formula produced significance 0.000 since the significance (2-tailed) value was smaller than (<) Alpha 0.05 Ho is rejected and Ha is accepted. Accordingly the research concludes that there is significant effect of using Picture Story Book on Grade Ten Students’ Reading comprehension at MAN 9 Jakarta in the academic year 2019/2020